Dokumentasi Keperawatan Berbasis Elektronik Meningkatkan Keselamatan Pasien dan Mutu Asuhan Keperawatan - Ike Puspitaningrum; Evi Supriatun; Sukma Diani Putri (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Electronic-based nursing care in hospitals refers to the application of information technology and electronic systems in the process of providing care for patients. There are various impacts in the use of electronic nursing records that have implications for patient safety. The purpose of this study was to review the impact of using electronic-based nursing documentation on patient safety and quality of nursing care. The method used is literature review by searching articles in three electronic databases: PubMed, ProQuest, and Science Direct. The inclusion criteria used were articles that matched the research objectives, according to the specified keywords, were in English, full text and published until 2022. There were eleven research articles that met the inclusion criteria. The results of a literature review on the eleven articles illustrate that electronic-based nursing documentation has a positive impact on patient safety and the quality of nursing care. The use of electronic nursing documentation provides various benefits, such as efficiency in managing patient data, increasing accuracy and speed in processing information, and improving coordination and communication between health workers. In addition, two articles also convey the impact of using electronic nursing documentation which is considered detrimental in an effort to maintain patient safety. Thus, the information in this literature review can be useful for planning the development of strategies for implementing electronic-based nursing documentation in hospitals.